Shear design method for non-prismatic concrete beams reinforced using W-FRP. (April 2021) - Yang, Yuanzhang; Shu, Jiangpeng; Zhao, Weijiang; Orr, John
Abstract: Flexible fabric formworks and bespoke Wound Fibre-Reinforced Polymer (W-FRP) cages have been proposed to address the difficulties of constructing geometrically optimised concrete structures with minimised material consumptions. However, the existing codes of practice for FRP reinforced concrete structures are not able to provide accurate shear behaviour predictions, resulting in potential premature anchorage failure. This paper presents a revised shear design approach for non-prismatic beams reinforced with W-FRP based on the Modified Compression Field Theory (MCFT), which considers the non-prismatic geometries, geometrical nonlinearity and internal load redistributions. The revised shear design approach is calibrated against previous fabric-formed T beam tests and parametric analyses are conducted to minimise the material usage of the previous T-beams. The validity of the shear design approach is further confirmed with a new T-beam test. The new test shows that the T beam designed with the MCFT based approach failed in the expected flexural failure mode with an ultimate capacity of 245 kN applied load. The predictions can effectively model the bar force development of the inclined flexural reinforcement with a Normalised Root Mean Square Error (NRSME) of 4.4%. The proposed shear design method improved the prediction accuracy of flexural bar force at ultimate capacity by 40% compared to the codified shear design method. By addressing the shear contributions of inclined flexural reinforcement and required anchorage strength, further applications of this novel flexibly formed beams with optimised geometries are expected to achieve material consumption reduction and hence lower carbon emissions from concrete structures.